Bilateral Hypocalemic Cataract Post Thyroidectomi : A Case Report: Poster Presentation - Case Report - Resident - Lestari, Andi Ayu; Ismail, Muh. Abrar; Poli, Adelina T.; Syamsu, Noor (Majalah Oftalmologi Indonesia, 2023)
Introduction : Young adult cataracts are negligible, and their prevalence is rarely reported in Indonesia. We reporta rapidly developing cataract in a 25-year-old woman due to secondary hypoparathyroidism. Cataracts in this case, progress remarkably fast compared to primary cataracts. Case Illustration : A twenty-five-year-old female patient presented bilateral vision loss and a history of a total thyroidectomy caused by diffused toxic goiter 7 years before admission. Postoperative calcium levels were extremely depleted. The uncorrected visual acuity examination measured 1/300 in the right eye and 20/200 in the left. Slit lamp examination revealed cortical opacities in both eyes. We diagnosedit as bilateral hypocalcemia cataracts. Patient has undergone bilateral phacoemulsification and intraocular lens implantation. The day following surgery visual acuity in the right eye was 20/30 and the left eye was 20/30 without correction. After one year of evaluation the visual acuity in RE become RE was 20/20 with a correction of -0.50 D sphere and the LE was 20/20 with a correction of -1.0 D sphere. Discussion : Patients with hypoparathyroidism risk developing cataracts due to chronic hypocalcemia, which inhibits the lenticular Na/K pump and induces intracellular sodium flux. This high sodium level triggers the osmosis process, followed by swelling of the lens fibers to form dystrophic calcifications. Thyroid surgery procedures suspectedly involving the parathyroid gland may cause hypocalcemia, thus leading to development of cataract. Conclusion : Clinicians should always consider hypoparathyroidism as the cause of bilateral cataracts in patients with a previous total thyroidectomy.